Comparing rating paradigms for evidence-based program registers in behavioral health: Evidentiary criteria and implications for assessing programs. (February 2015) - Means, Stephanie N.; Magura, Stephen; Burkhardt, Jason T.; Schröter, Daniela C.; Coryn, Chris L.S.
Highlights: Registers tend to recognize the "traditional" Campbellian hierarchy of evidence. Registers sometimes disagree on the criteria that define program effectiveness and research quality. Registers use statistical significance as evidence of effectiveness, but usually ignore program effect size. Registers avoid assessing qualitative evidence. Using meta-analyses to guide program-level decision-making can be problematic. Abstract: Decision makers need timely and credible information about the effectiveness of behavioral health interventions. Online evidence-based program registers (EBPRs) have been developed to address this need. However, the methods by which these registers determine programs and practices as being "evidence-based" has not been investigated in detail. This paper examines the evidentiary criteria EBPRs use to rate programs and the implications for how different registers rate the same programs. Although the registers tend to employ a standard Campbellian hierarchy of evidence to assess evaluation results, there is also considerable disagreement among the registers about what constitutes an adequate research design and sufficient data for designating a program as evidence-based. Additionally, differences exist in how registers report findings of "no effect, " which may deprive users of important information. Of all programs on the 15 registers that rate individual programs, 79% appear on only one register. Among a random sample of 100 programs rated by more than one register, 42% were inconsistently rated by the multiple registers to some degree.